Identification of Tree Species by Their Defense Compounds: A Study with Leaf Buds of White and Silver Birches - Manninen Marianna; Vesterinen Veli-Matti; Vainio Anna-Kaisa; Korhonen Heidi; Karonen Maarit; Salminen Juha-Pekka (AMER CHEMICAL SOC, 2022)
Plants encounter several different threats that affect their well-being during the spring. With chemistry, plants may defend themselves from, for example, excess UV-radiation and herbivores. The defense compounds between plant species vary, which makes it possible to utilize chemistry in identifying the plant species. In this laboratory experiment, students extracted the defense compounds from the surface of leaf buds, estimated the total phenolic content of the extract, and determined its antioxidant activity. In addition, the chemical fingerprints of the leaf buds were analyzed by liquid chromatography combined to mass spectrometry to identify the species as white birch, silver birch, or some other tree species. The laboratory experiment was performed with secondary school and university students in one approximately 3 h laboratory session. Pre- and post-tests done by the university students showed that the experiment provided students a basic understanding of how the instruments function and what they are used for. Their mind maps of the chemistry of plants were concentrated on the primary metabolites, but the experiment widened their views of specialized metabolites and their functions in plants, thus encouraging the students to combine chemical and biological information.